Bibliometric Evaluation vs. Informed Peer Review: Evidence from Italy - Graziella Bertocchi; Alfonso Gambardella; Tullio Jappelli; Carmela A. Nappi; Franco Peracchi (Institute for the Study of Labor (IZA), 2013)
A relevant question for the organization of large scale research assessments is whether bibliometric evaluation and informed peer review where reviewers know where the work was published, yield similar results. It would suggest, for instance, that less costly bibliometric evaluation might - at least partly - replace informed peer review, or that bibliometric evaluation could reliably monitor research in between assessment exercises. We draw on our experience of evaluating Italian research in Economics, Business and Statistics, where almost 12,000 publications dated 2004-2010 were assessed. A random sample from the available population of journal articles shows that informed peer review and bibliometric analysis produce similar evaluations of the same set of papers. Whether because of independent convergence in assessment, or the influence of bibliometric information on the community of reviewers, the implication for the organization of these exercises is that these two approaches are substitutes.
Keywords: I23; C80; O30; 330; research assessment; peer review; bibliometric evaluation; VQR